From sustainable urbanism to climate urbanism. (April 2019) - Long, Joshua; Rice, Jennifer L
As the negative impacts of climate change become increasingly apparent, many city leaders and policymakers have begun to regard climate action as both a fiscal challenge and strategic economic opportunity. However, addressing the increasingly evident threats of climate change in the neoliberal, post-financial-crisis city raises several questions about its equitable implementation. This paper suggests that the prioritisation of a specific mode of climate resilient urban development represents a departure from the previous decades' movement toward sustainable urbanism. We refer to this new development paradigm as 'climate urbanism', a policy orientation that (1) promotes cities as the most viable and appropriate sites of climate action and (2) prioritises efforts to protect the physical and digital infrastructures of urban economies from the hazards associated with climate change. We argue that the potential social justice impacts of climate urbanism have not been fully interrogated. Certainly, cities are appropriate sites for addressing climate change, but in the current neoliberal context, the transition from policy rhetoric to climate action presents a potentially problematic landscape of inequality and injustice. With that in mind, this paper offers a critical lens to evaluate the merits of climate urbanism and to interrogate its potential outcomes.